Damage Mechanisms Avoided or Managed for NIF Large Optics. (1st February 2016) - Manes, K. R.; Spaeth, M. L.; Adams, J. J.; Bowers, M. W.; Bude, J. D.; Carr, C. W.; Conder, A. D.; Cross, D. A.; Demos, S. G.; Nicola, J. M. G. Di; Dixit, S. N.; Feigenbaum, E.; et al.
Abstract: After every other failure mode has been considered, in the end, the high-performance limit of all lasers is set by optical damage. The demands of inertial confinement fusion (ICF) pushed lasers designed as ICF drivers into this limit from their very earliest days. The first ICF lasers were small, and their pulses were short. Their goal was to provide as much power to the target as possible. Typically, they faced damage due to high intensity on their optics. As requests for higher laser energy, longer pulse lengths, and better symmetry appeared, new kinds of damage also emerged, some of them anticipated and others unexpected. This paper will discuss the various types of damage to large optics that had to be considered, avoided to the extent possible, or otherwise managed as the National Ignition Facility (NIF) laser was designed, fabricated, and brought into operation. It has been possible for NIF to meet its requirements because of the experience gained in previous ICF systems and because NIF designers have continued to be able to avoid or manage new damage situations as they have appeared.